2023
DOI: 10.3390/diseases11030102
|View full text |Cite
|
Sign up to set email alerts
|

Post-Infection Oscillometry and Pulmonary Metrics in SARS-CoV-2 Patients: A 40-Day Follow-Up Study

Abstract: The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has had significant impacts on pulmonary function. This study aimed to comprehensively evaluate pulmonary function and structure in patients 40 days post-SARS-CoV-2 infection, employing an array of testing methodologies including spirometry, plethysmography, forced oscillometry, and CT scanning. It also sought to establish potential correlations between these metrics and evaluate if forced oscillometry could provide additional value in post-infective lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In line with our findings, Bonato et al [41] found that persistent dyspnea in PACS (which can be relieved by an PR program) is associated with small airway dysfunction 3 months after discharge, regardless of the parenchymal/radiological sequelae. A follow-up observational study of PACS individuals showed that, in the multiple regression analysis, reactance at 4 Hz, forced expiratory flow during the middle half of the FVC maneuver and Fres were significantly related to the severity of COVID-19 [42]. We believe that it is likely that the improvement in respiratory mechanics of these patients with PR, especially peripheral and tissue resistance (chest wall), may increase exercise tolerance with a positive impact on functional independence and QoL.…”
Section: Plos Onementioning
confidence: 99%
“…In line with our findings, Bonato et al [41] found that persistent dyspnea in PACS (which can be relieved by an PR program) is associated with small airway dysfunction 3 months after discharge, regardless of the parenchymal/radiological sequelae. A follow-up observational study of PACS individuals showed that, in the multiple regression analysis, reactance at 4 Hz, forced expiratory flow during the middle half of the FVC maneuver and Fres were significantly related to the severity of COVID-19 [42]. We believe that it is likely that the improvement in respiratory mechanics of these patients with PR, especially peripheral and tissue resistance (chest wall), may increase exercise tolerance with a positive impact on functional independence and QoL.…”
Section: Plos Onementioning
confidence: 99%
“…Certain investigations have yielded compelling evidence of significantly elevated small airway resistance in COVID‐19 positive individuals both during the acute infection phase and after a 2‐month follow‐up, 3 as well as a 40‐day follow‐up. 4 Meanwhile, alternative research has directed its focus towards chest imaging and lung ultrasound in post‐COVID‐19 patients. 5 , 6 However, other studies did not find a significant increase in small airway resistance among COVID‐19 inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…decrease in respiratory challenges post-recovery across the years is promising, potentially hinting at better post-COVID respiratory care or natural improvement over time, as well as the recent development of cardiopulmonary rehabilitation techniques. [32][33][34] From an emotional perspective, the marked decrease in feelings of sadness, hopelessness, or depression affecting daily life is encouraging. This trend might reflect the resilience of the human spirit, the effectiveness of coping mechanisms, or improved support systems as the pandemic progressed, concurrently with the feeling of hope after the vaccination campaign and the pandemic reaching to an end.…”
mentioning
confidence: 99%